Hallucination in a Seizure Patient Using Levetiracetam: A Case Report - D. R. Shakya; A. Dutta; R. Gautam (Case Reports in Medicine)
Levetiracetam, a relatively new antiepileptic drug (AED), is used mainly as adjuvant and less as monotherapy of seizure. Though rare, Levetiracetam is reported to induce hallucination. To highlight the potential of this adverse drug event, we report a seizure-case that had auditory hallucination with Levetiracetam. A 32-year lady had 7-year history of unresponsive spells which increased in the last year, also occurred while asleep and were diagnosed as “generalized seizure” with video-EEG. With gradual optimization of Levetiracetam to 2250 mg, she continuously heard distressing sound of saw cutting wooden blocks. After 3-day continuous auditory hallucination, Levetiracetam had to be changed to sodium valproate.